Comparative structural analysis of vascular aquatic flora in upper and middle parts of Southern Bug valley (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
The comparative structural analysis of the vascular aquatic flora in upper and middle parts of Southern Bug valley is presented. The flora comprises 106 species of 59 genera and 34 families. Patterns of aquatic macrophytes’ territorial differentiation within the river valley are elucidated.
Keywords: Southern Bug, vascular aquatic flora, comparative structural analysis.